2008
DOI: 10.1051/parasite/2008152099
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma (Megatrypanum) saloboensen. sp. (Kinetoplastida: Trypanosomatidae) parasite ofMonodelphis emiliae(Marsupiala: Didelphidae) from Amazonian Brazil

Abstract: Summary :Trypanosoma (Megatrypanum) saloboense n. sp., is described in the Brazilian opossum Monodelphis emiliae (Thomas, 1912)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…has been documented (Hoare, 1972;Ziccardi and Lourenco-de-Oliveira, 1999;Zintl et al 2000;Lainson et al 2008). Trypomastigote pleomorphism was noted in the present study when comparisons were made of morphometric measurements of T. copemani from koalas with those of T. copemani from Gilbert's potoroo and quokka.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…has been documented (Hoare, 1972;Ziccardi and Lourenco-de-Oliveira, 1999;Zintl et al 2000;Lainson et al 2008). Trypomastigote pleomorphism was noted in the present study when comparisons were made of morphometric measurements of T. copemani from koalas with those of T. copemani from Gilbert's potoroo and quokka.…”
Section: Discussionmentioning
confidence: 77%
“…Although the importance of trypomastigote morphology should not be discounted, the utility of delineating trypanosome species based on morphometrics alone is highly questionable as pleomorphism of bloodstream trypomatigotes of numerous T. spp. has been documented (Hoare, 1972; Ziccardi and Lourenco-de-Oliveira, 1999; Zintl et al 2000; Lainson et al 2008). Trypomastigote pleomorphism was noted in the present study when comparisons were made of morphometric measurements of T. copemani from koalas with those of T. copemani from Gilbert's potoroo and quokka.…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of trypomastigote morphology should not be discounted, delineating trypanosome species based on morphometrics alone is not reliable, as pleomorphism of bloodstream trypomastigotes of numerous T. spp. has been documented (Hoare, 1972;Ziccardi and Lourençode-Oliveira, 1999;Zintl et al, 2000;Lainson et al, 2008;Austen et al, 2009;McInnes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, the wide morphobiometric heterogeneity among parasites of the genus Trypanosoma restricts, to some extent, the use of this parameter, although it has been employed as a complementary tool for the differentiation and identification of various species of this genus (Ziccardi and Lourenço-de-Oliveira, 1998), especially the differentiation between T. cruzi and T. rangeli (Sousa et al 2008). In a recent study, elegantly exploring these parameters, Lainson et al (2008) demonstrated the circulation of a new Trypanosoma species of the subgenus Megatrypanum .…”
Section: Discussionmentioning
confidence: 99%